Time management and academic commitment in psychology students from a private university in Juliaca - Daniel Eduardo, Cahuana Cuti (2022)
Objective: to determine if there is a significant relationship between time management and academiccommitment in psychology students from a private university. Methodology: non-experimental design,cross-sectional, correlational type and quantitative approach. The sample consisted of 217 students,who were selected through stratified probability sampling where they were divided into 5 populationgroups of psychology students aged 18 years and over, taking into account men and women who areenrolled in the student cycle 2021-1. The instruments used were the Time Management Behavior Scale(TMBS), this instrument reaches a confidence index of .867 and a validity of V = .99. Regarding theUtrecht Work Engagement Student (UWES) instrument, this instrument achieves a confidence index of.917 and a validity of V = .99; These instruments indicate a degree of validity and reliability that showsthat both instruments measure what they should measure consistently. Results: time managementand academic commitment are positively and statistically significantly correlated (r = .335, p = .000).Likewise, there is a correlation in the vigor dimension (Rho = .373; p = .000), dedication (Rho =. 231;p = .000) and Absorption (Rho = .287; p = .000), being highly significant. Conclusion: the greater thetime management, the greater the academic commitment.